2022
DOI: 10.1088/1741-4326/ac6f68
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the emissivity measurements performed in WEST: in situ and post-mortem observations

Abstract: This paper summarizes the emissivity measurements performed on the plasma facing units (PFU) of the WEST lower divertor during the first phase of WEST running with a mix of actively cooled ITER-like PFUs made of bulk tungsten and inertially cooled PFUs made of graphite with a coating of tungsten. In-situ assessment of the emissivity and laboratory measurements after removing the W-coated graphite and ITER-grade PFUs from the WEST device are shown. The measurements exhibit a complex pattern with strong emissivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Figure 1 shows an estimate of the total error on the measured temperature including the errors coming from the measurement chain (transmission, parasitic light) and coming from the observed thermal scene (emissivity, reflected flux) for the equatorial wide-angle viewing systems. We consider an uncertainty on the emissivity value ∆ε of 0.15 for a tungsten target around of 0.2 emissivity, which is in agreement with laboratory and tokamak measurements [2]. The total transmission of optical system is fixed to 10% with an error ∆τ of 50%, including the calibration uncertainties and the flux losses due to spatial resolution [3].…”
Section: Estimation Of Temperature Measurement Error From Ir Imaging ...mentioning
confidence: 76%
See 1 more Smart Citation
“…Figure 1 shows an estimate of the total error on the measured temperature including the errors coming from the measurement chain (transmission, parasitic light) and coming from the observed thermal scene (emissivity, reflected flux) for the equatorial wide-angle viewing systems. We consider an uncertainty on the emissivity value ∆ε of 0.15 for a tungsten target around of 0.2 emissivity, which is in agreement with laboratory and tokamak measurements [2]. The total transmission of optical system is fixed to 10% with an error ∆τ of 50%, including the calibration uncertainties and the flux losses due to spatial resolution [3].…”
Section: Estimation Of Temperature Measurement Error From Ir Imaging ...mentioning
confidence: 76%
“…WEST experience has shown that the emissivity of metallic targets changes after plasma, mainly due to the erosiondeposition phenomenon that occurs during the reactor lifetime [2]. A challenge for getting more reliable IR measurements and safe operation is to be able to follow emissivity change during the experimental campaign.…”
Section: Emissivity Assessmentmentioning
confidence: 99%
“…The behavior of both emission and reflection can vary significantly with surface roughness, the machining process, and as the plasma operation progresses [17]. Researchers at WEST reported spatial gradients in the emissivity of exposed ITER-grade plasma-facing units that ranged from 0.05-0.85 [18]. However, this level of emissivity variation is not as severe in the case of devices like NSTX-U and DIII-D where the PFC armor is made of graphite.…”
Section: Thermography and Its Challengesmentioning
confidence: 99%
“…The WEST tokamak has superconducting magnets and actively cooled metallic PFCs which operate with steady-state long pulses and high particle fluence; its aim is to test the W divertor technology in an integrated tokamak environment [22][23][24]. A thorough testing of the changes in the surface morphology and composition of PFCs has been carried out by various methods [25][26][27]. LIBS is one method planned for the testing of elemental composition of selected divertor samples and the fuel retention in them.…”
Section: Introductionmentioning
confidence: 99%